2015
DOI: 10.1016/j.chemosphere.2014.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Changes of polybrominated diphenyl ether concentrations in ducks with background exposure level and time

Abstract: h i g h l i g h t sWe conducted a semi-field experiment of ducks in an e-waste recycling site. PPBDEs increased in fat with time, but fluctuated in other tissues with exposure level. High brominated DE levels increased with time but low brominated DE fluctuated in fat. High brominated DEs seem to have longer half-lives than low brominated DEs in fat. a r t i c l e i n f o b s t r a c tTo reveal what degree bioaccumulation of polybrominated diphenyl ethers (PBDEs) depends on exposure time and other factors, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Previous studies reported high levels of PBDEs in soil, sediment and air samples from this area, with BDE-209 as the dominant congener (Han et al, 2009;Tang et al, 2014;Yu et al, 2016). High levels of PBDEs have also been found in wildlife and domestic animals in this area (Liu et al, 2011(Liu et al, , 2015Qin et al, 2011;Yang et al, 2011), suggesting that Taizhou would be an appropriate locale for investigating the bioaccumulation of PBDEs. In particular, collecting biotic samples from different animals from the same site facilitates the comparison of species-specific differences in bioaccumulations of PBDEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported high levels of PBDEs in soil, sediment and air samples from this area, with BDE-209 as the dominant congener (Han et al, 2009;Tang et al, 2014;Yu et al, 2016). High levels of PBDEs have also been found in wildlife and domestic animals in this area (Liu et al, 2011(Liu et al, , 2015Qin et al, 2011;Yang et al, 2011), suggesting that Taizhou would be an appropriate locale for investigating the bioaccumulation of PBDEs. In particular, collecting biotic samples from different animals from the same site facilitates the comparison of species-specific differences in bioaccumulations of PBDEs.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue samples were extracted, cleaned and analyzed according to previously reported methods (Liu et al, 2011(Liu et al, , 2015 with minor modifications. Briefly, after freeze-drying, homogenizing with anhydrous sodium sulfate and spiking with surrogate standard ( 13 C-labeled BDE-209) and recovery standard (BDE-71), samples were extracted twice with n-hexane/dichloromethane (1:1, vol/vol) by ultrasonic agitation.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…In China, the occurrence of PBDEs in surface water has been investigated in the three major river systems Pearl River, Yellow River, and Yangtze River at mean concentrations of Σ 7 PBDE (excluding 209) up to 0.08 ng/L [ 24 ], 1.26 ng/L [ 25 ], and 6.44 ng/L [ 26 ], respectively. The concentrations of PBDEs in Chaohu Lake basin were situated between the above concentrations, but were lower than those in the water of e-waste dismantling areas [ 27 ]. In addition, suspended particulate matter (SPM) samples collected from Chaohu Lake were investigated by He et al [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that chlorpyrifos had a low persistency in the livestock meat and the metabolism organs and that depletion of parent compound residues from the body occurred rapidly, which was different from bioaccumulation of persistent pollutant (e.g., polybrominated diphenyl ether) in ducks. 27 The HR (0.016 mg/kg) in fat of the 1× dose group was slightly higher than the MRL (0.01 mg/kg) set by CAC and Japan and lower than the MRL (0.05 and 0.1 mg/kg) set by the European Union (EU) and the United States, respectively. The HR (0.11 mg/kg) in fat of the 10× dose group was higher than the MRL (0.1 mg/kg) set by the United States.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 96%